AKTUALISASI NILAI PANCASILA DALAM ACARA ADAT SAMMILAN PADA MASYARAKAT ADAT MAGHO SEKAPPUNG LIBO - Eka Yuliastuti; Wahyu Abdul Jafar (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The problem examined in this research is the problem of the actualization of Pancasila values contained in the Sammilan traditional culture and its relevance to the values of local wisdom in the Batin Negara Village. This research belongs to the category of field research, and the approach used in this research is the sociological approach. Data collection techniques used were interview and documentation techniques. After conducting the research, it was concluded that the Sammilan traditional culture contains many positive values that can be applied in living the life of society and the state, the traditional culture of Sammilan is present in the midst of the people who are still very caring and caring for Indonesia in various aspects of life. In carrying out the traditional sammilan event is considered still in harmony and relevant to the values of Pancasila. The tolerance attitude of the people of Sekappung Libo is reflected if there are neighbors who are carrying out an adat event, they are not afraid without being asked to respect each other, help each other and help one another. Keywords: Actualization of Pancasila Values; Indigenous Sammilan